Neuropeptide S and BDNF gene expression in the amygdala are influenced by social decision-making under stress - Smith, Justin P.; Achua, Justin K.; Summers, Tangi R.; Ronan, Patrick J.; Summers, Cliff H. (Frontiers in Behavioral Neuroscience, 2014)
In a newly developed conceptual model of stressful social decision-making, the Stress-Alternatives Model (SAM; used for the 1st time in mice) elicits two types of response: escape or remain submissively. Daily (4d) aggressive social interaction in a neutral arena between a C57BL6/N test mouse and a larger, novel aggressive CD1 mouse, begin after an audible tone (conditioned stimulus; CS). Although escape holes (only large enough for smaller test animals) are available, and the aggressor is unremittingly antagonistic, only half of the mice tested utilize the possibility of escape. During training, for mice that choose to leave the arena and social interaction, latency to escape dramatically decreases over time; this is also true for control C57BL6/N mice which experienced no aggression. Therefore, the open field of the SAM apparatus is intrinsically anxiogenic. It also means that submission to the aggressor is chosen despite this anxiety and the high intensity of the aggressive attacks and defeat. While both groups that received aggression displayed stress responsiveness, corticosterone levels were significantly higher in animals that chose submissive coexistence. Although both escaping and non-escaping groups of animals experienced aggression and defeat, submissive animals also exhibited classic fear conditioning, freezing in response to the CS alone, while escaping animals did not. In the basolateral amygdala (BLA), gene expression of brain-derived neurotrophic factor (BDNF) was diminished, at the same time neuropeptide S (NPS) expression was significantly elevated, but only in submissive animals. This increase in submission-evoked NPS mRNA expression was greatest in the central amygdala (CeA), which coincided with decreased BDNF expression. Reduced expression of BDNF was only found in submissive animals that also exhibit elevated NPS expression, despite elevated corticosterone in all socially interacting animals. The results suggest an interwoven relationship, linked by social context, between amygdalar BDNF, NPS and plasma corticosterone.